SYNTHESIS OF SOME NOVEL BENZOPYRANES DERIVATIVES AND EVALUATION THEIR BIOLOGICAL ACTIVITY - Ahmed, Hatem Abdel Moniem (Asian Journal of Pharmaceutical and Clinical Research, 2015)
ABSTRACT Benzopyran (chromene) is one of the privileged medicinal pharmacophore, which appears as an important structural component in natural compounds and generated great attention because of their interesting biological activity. The derivatives of benzopyran moiety can be capable of interacting with a variety of cellular targets which leads to their wide ranging biological activities such as antitumor, antihepatotoxic, antioxidant, antiinflammatory, diuretic, anticoagulant, antispasmolytic, estrogenic, antiviral, antifungal, antimicrobial, anti-helminthic, hypothermal, vasodilatory, anti-HIV, antitubercular, herbicidal, anticonvulsant and analgesic activity. In the present study the synthesis of substituted benzopyran derivatives have been reported as one-pot reaction by reaction of 2-chlororesorcinol with malononitrile in the presence and aldehydes or ketones. The produced products were led to react with formamide to produce pyrimidochromene. Aminochromene-2-carbonitrile was converted into the corresponding imidate, which in turn converted upon treatment withhydrazine or ammonia to the corresponding amidine. The produced amidines were cyclized into the pyrimidochromene derivatives. The synthesized compounds have been characterized by TLC, Elemental analysis, IR and 1H-NMR Spectroscopy. Some of the synthesized compounds in this work were chosen and screened in vitro for their antimicrobial and anti-fungal activity against some strains of bacteria and fungi. The antibacterial and anti-fungal activities of synthesized compounds were compared with antibacterial and anti-fungal activity of the standard antibiotics Chloramphenicol and Sertaconazol. The most of the tested compounds revealed antibacterial and antifungal properties. This review is summarized to know about the different pharmacological activities of chromene nucleus with the extended knowledge about its antimicrobial and antifungal activity. Keywords: 2-Chlororesorcinol, Pyrimidochromene, Amidines, antimicrobial and antifungal activity.